The Dynamics of Land Tenure and Utilization: A Case Study of Agrarian Disputes in Aceh Besar District: - - Novianti, Leny (Teunuleh Publisher, 2024)
Agrarian disputes in Indonesia are still a complex problem that has a direct impact on social inequality and legal uncertainty, including in Aceh Besar District. This study aims to analyze the dynamics of land tenure and utilization which are the roots of agrarian conflict in the region. The approach used is qualitative with a case study method, through field observations, in-depth interviews with communities, local government, legal officials, and the private sector, as well as analysis of legal documents and land policies. The results show that overlapping claims between customary and formal legal rights, weak legal protection of historically-based land tenure, and the dominance of economic interests in land use are the main causes of conflict. Available dispute resolution mechanisms have not been effective, both litigative and non-litigative, because they do not accommodate the root of the problem and tend to ignore participatory aspects. On the other hand, local institutions such as mukim and tuha peut have the potential to be key actors in conflict resolution, but have not received adequate regulatory support. This finding confirms the need for fairer and more inclusive agrarian policy reform, by encouraging harmonization between state law and customary law, community empowerment, and strengthening local institutions as a strategy for resolving agrarian conflicts in a sustainable manner.